Pharmacokinetics of CYP2C9, CYP2C19, and CYP2D6 substrates in healthy Chinese and European subjects - Lu, Sijie; Nand, R. A.; Yang, J. S.; Chen, Gang; Gross, A. S. (European journal of clinical pharmacology, 2018)
Purpose The aim of this analysis is to compare the pharmacokinetics of drug substrates in healthy Chinese and European subjects of aligned CYP2C9, CYP2C19, or CYP2D6 enzyme activity, providing further insight into drivers of interethnic differences in pharmacokinetics. Methods Following identification of appropriate drug substrates, a comprehensive and structured literature search was conducted to identify single-dose pharmacokinetic data in healthy Chinese or European subjects with reported CYP2C9, CYP2C19, or CYP2D6 activity (genotype or phenotype). The ratio of drug AUC in the Chinese and European subjects classified with aligned enzyme activity was calculated (ethnicity ratio (ER)). Results For 22/25 drugs identified, the ERs calculated indicated no or only limited interethnic differences in exposure (<twofold) in Chinese and European subjects with aligned polymorphic enzyme activity. The interethnic differences observed can reflect differences across populations in additional determinants of pharmacokinetics, although the notable between study variation and change over time in methods used to assign enzyme activity may also be contributing factors. There was no association between drug substrate fraction metabolized (fm) for CYP2C9, CYP2C19, or CYP2D6 and the ERs calculated. Conclusion The spectrum of pharmacokinetic determinants for each drug substrate and their differences across ethnic groups must be considered on a case-by-case basis in addition to metabolism by CYP2C9, CYP2C19, or CYP2D6. This analysis has also highlighted the challenges which arise when comparing published datasets if consistent methods to assign polymorphic enzyme activity have not been used.